Representaciones sociales hacia la cultura del metal de un grupo de "metaleros" de Bogotá (2009)
This is an empirical, descriptive, transversal study, whose purpose is to find the social representations held by a group of metal followers in Bogota with regards to the metal genre. Participants were 111 metal followers, aged 18 to 30 years, who completed a free word association test. Results suggested that the social representations studied relate to a disagreement position with the rules of society, as well as the energy and power generated by metal music.